Determining Distribution Center Locations to Optimize Food Supply Chain Integration (A Case Study of an Agribusiness Company in Indonesia) - Yelita Anggiane Iskandar; Nur Layli Rachmawati; Adji Candra Kurniawan; Ravi Prananda Kurniawan; Mega Rizkah Sudiar; Dedy Ramadhan; Sayyid Firous Taufiqulhaqiem; Andi Nur Shafirah Ramdhani Abidin; Anissa Widiyanti (Majalah Ilmiah Bijak, 2023)
PT Asagri Selaras Asia is an agribusiness company in Jakarta, Indonesia that provides food supply for entrepreneurs in the tourism sector, such as hotels and restaurants. In running their business, the company has a supply chain network that effectively integrates suppliers, manufacturers, warehouses, and stores. Supply chain management optimization is deemed necessary to maximize efficiency in every process carried out at PT Asagri Selaras Asia. One of the processes that can be optimized is the determination of facility location. The right facility location can minimize distance, delivery time, and operational costs and optimize the company's profit. Currently, the contract period for the distribution center (DC) used by PT Asagri Selaras Asia is about to expire therefore a decision is needed regarding the determination of the DC location for the next period, either extending the current DC contract or moving to a new location. This study aims to maximize the company's profit by comparing the profit obtained under existing and alternative DC, and the proposed DC from the experimental results using the Green Field Analysis (GFA) method. This study also aims to determine the feasibility of the three DC locations using the Network Optimization (NO) method with Anylogistix software. Based on the data analysis, the new DC is recommended to be located in the West Pejaten area, South Jakarta with latitude -6.2729150574 and longitude 106.8230798418 which will give an increase in profit of 80.53% compared to the existing DC.